Ledarskap vid räddningsinsatser : En fallstudie vid Räddningstjänsten i Luleå - Erkheikki, Emilia (2012)
The aim of this thesis was to examine the leadership before, during, and after a rescue operation. The questions raised was: What aspects of the leaders everyday leadership is most important in their leadership during and after a rescue operation and how will it manifest itself?, How do the firefighters perceive the leadership before, during and after a rescue operation and What do they value about the leaders?, and How do the leaders perceive the current leadership structure and how does it affect their leadership? To answer the questions a total of 24 interviews were conducted with internal officers, operation leaders, team leaders, and firefighters. The results show that trust within the team was of central importance for the team leader’s leadership. The firefighters were generally satisfied with their team leader. The leader was partly perceived as available, willing to listen to the opinions of the firefighters, and trustworthy. A majority of the operation and team leaders perceived the current leadership structure as unclear. Validerat; 20120911 (anonymous)